The Effectiveness of Shadowing Techniques on Speaking Fluency of 11th Grade Students at SMA Negeri 1 Bambanglipuro - Harniken Farensya; Sukarno Sukarno (Interdiciplinary Journal and Hummanity (INJURITY), 2026)
This study aimed to examine the effectiveness of the shadowing technique in improving the speaking fluency of eleventh-grade students at State of Senior High School 1 Bambanglipuro. Speaking fluency remains a significant challenge for English as a Foreign Language (EFL) learners, particularly in producing smooth, continuous, and coherent speech with minimal hesitation. Therefore, this study focused on investigating whether the implementation of the shadowing technique could significantly enhance students’ speaking fluency compared to conventional teaching methods. This study employed a quantitative approach using a quasi-experimental two-group pretest–posttest design. The research was conducted at State of Senior High School 1 Bambanglipuro, Yogyakarta, involving two classes of eleventh-grade students, consisting of 32 students in the experimental group and 27 students in the control group. Data were collected through speaking tests administered as pre-test and post-test. The research instrument was a monologue speaking test assessed using an analytic scoring rubric covering speech rate, pausing and hesitation, continuity, and automaticity. The data were analyzed using descriptive and inferential statistics through Analysis of Covariance (ANCOVA). The results showed that the experimental group improved significantly from a mean score of 54.06 to 83.44, while the control group showed only a slight improvement from 58.52 to 63.89. The ANCOVA results revealed a statistically significant effect of the instructional technique on students’ speaking fluency (F = 22.456; p < 0.001; ?² = 0.290). It can be concluded that the shadowing technique is effective in improving students’ speaking fluency